A non-pharmacological multidomain intervention of dual-task exercise and social activity affects the cognitive function in community-dwelling older adults with mild to moderate cognitive decline: A randomized controlled trial - Lee, Sangyoon; Harada, Kenji; Bae, Seongryu; Harada, Kazuhiro; Makino, Keitaro; Anan, Yuya; Suzuki, Takao; Shimada, Hiroyuki (Frontiers in Aging Neuroscience, 2023)
The present study aimed to determine the impact of a 10-month multidomain program using dual-task exercise and social activity conducted at a community-based facility on improved cognitive function in older adults with mild to moderate cognitive decline. The participants included 280 community-dwelling older adults (age 71–91 years) with mild to moderate cognitive decline. The intervention group exercised for 90 min/day, once a week. Their routine included aerobic exercise and muscle strength training, and was conducted under dual-task conditions to stimulate cognitive function. The control group attended health education classes thrice. Before and after the intervention, we measured their cognitive function, physical function, daily conversation, and physical activity. The mean adherence rate of the intervention class was 83.0%. According to a repeated-measures multivariate analysis of covariance in an intent-to-treat analysis, logical memory and 6-min walking distance demonstrated a significant time and group interaction effect. Regarding daily physical activities, we observed significant differences in the daily step count and moderate-to-vigorous physical activity in the intervention group. Our non-pharmacological multidomain intervention resulted in a modest improvement in the cognitive or physical function and building health behavior. It may be a helpful program with a potential role in preventing dementia.